Wireless temperature sensor network - Anis Suhaila, Mohd Zain; Mardiana, Bidin; Niza, Mohd Idris; Siti Khadijah, Idris @ Othman; Zahariah, Manap (2006)
Sensor networks are being widely deployed for measurement, detection and surveillance applications. Today, humidity becomes very important in many aspects especially in manufacturing industry. Therefore, the use of tools or systems that can monitor the humidity level is very significant. Sensor networks can be used to identify larger trends in temperature which could be used to report energy usage, HVAC problems, computer failures based on high temperatures and fire evacuation route reporting. This project presents a design of Wireless Temperature Sensor Network that capable to monitor the humidity level. This Wireless Temperature Sensor Network comprises of two parts; temperature detection and monitoring. The detection section will sense the temperature and transmit the signal to the monitoring section. All the sensors are connected mote to mote to ensure that each mote can communicate and exchange the data with each other. The collection of temperature data would be obtained by a sensor network. The data was collected using a temperature sensor network connected to a stand-alone computer. This approach can makes the monitoring process becomes more efficient and cost effective. The data (temperature level) will be display by using GUI. In the case of mote to mote system, the GUI capable to display the overall level of temperature.